2019
DOI: 10.1038/s41598-019-53035-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective pollination of Aeschynanthus acuminatus (Gesneriaceae) by generalist passerines, in sunbird-absent East Asia

Abstract: Aeschynanthus (Gesneriaceae), a genus comprising approximately 160 species in subtropical Southeast Asia, has red, tubular flowers, typical of a sunbird pollination syndrome. A. acuminatus, the species that is distributed extending to the northern edge of the genus, where the specialized nectarivorous sunbirds are absent, possesses reddish-green flowers and a wide-open corolla tube, flowering time shifts from summer to winter and the species achieves high fruiting success. This atypical flower led us to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown, however, that the tendency to hover or perch while feeding depends primarily on plant architecture, not on energetic limitations due to body mass (Miller, 1985;Wester, 2013;Westerkamp, 1990). Most hummingbirds perch on any structure that they can reach with their short feet while extracting nectar from a flower (e.g., Feinsinger & Colwell, 1978;Stiles, 2008), and sunbirds and honeyeaters can hover for brief periods (e.g., <1 min; Geerts & Pauw, 2009), but it occurs facultatively when a plant does not supply suitable perches (Anderson et al, 2005;Chang et al, 2013;K.-H. Chen, Lu, et al, 2019;Ford & Paton, 1977;Geerts & Pauw, 2009;Janeček et al, 2011;Padyšáková & Janeček, 2016;Pyke, 1980;Sejfová et al, 2021;Wester, 2013). To accomplish hovering, sunbirds and honeyeaters use a typical asymmetric flight stroke (lift generated on downstroke only; Norberg, 1990) and generate sufficient lift by increasing wingbeat frequency (Zimmer, 1943).…”
Section: Wing Morphology and Flightmentioning
confidence: 99%
“…Studies have shown, however, that the tendency to hover or perch while feeding depends primarily on plant architecture, not on energetic limitations due to body mass (Miller, 1985;Wester, 2013;Westerkamp, 1990). Most hummingbirds perch on any structure that they can reach with their short feet while extracting nectar from a flower (e.g., Feinsinger & Colwell, 1978;Stiles, 2008), and sunbirds and honeyeaters can hover for brief periods (e.g., <1 min; Geerts & Pauw, 2009), but it occurs facultatively when a plant does not supply suitable perches (Anderson et al, 2005;Chang et al, 2013;K.-H. Chen, Lu, et al, 2019;Ford & Paton, 1977;Geerts & Pauw, 2009;Janeček et al, 2011;Padyšáková & Janeček, 2016;Pyke, 1980;Sejfová et al, 2021;Wester, 2013). To accomplish hovering, sunbirds and honeyeaters use a typical asymmetric flight stroke (lift generated on downstroke only; Norberg, 1990) and generate sufficient lift by increasing wingbeat frequency (Zimmer, 1943).…”
Section: Wing Morphology and Flightmentioning
confidence: 99%
“…The blooming B. ceiba attracted many tourists and when B. ceiba starts blooming, local farmers transplanted rice seedlings in nearby paddies, resulting in decrease in bird visitation frequency and duration; (2) A massive number of flowers on one tree allows birds to meet their nectar needs without moving frequently between trees, which was proved by the restricted pollen dispersal distance (Figure 2 and Figure 3). The high efficiency of pollen removal and low combing behavior of birds (Chen et al, 2019;Song et al, 2019) also made the birds carry a large amount of pollen grains from few pollen donors on their bodies and, thus, have the potential to pollinate multiple ovules in a single visit. One of our observations, where 30 randomly seeds of > 300 seeds of a plant were all from the same father, supported this possibility (Figure 2 and Table 3); and (3) The investigated plant population is not a completely closed population (Figure 2) and some pollen donors might from unlabeled individuals within study population or nearby populations, which might cause underestimation of multiple paternity in our results.…”
Section: Multiple Paternitymentioning
confidence: 99%
“…However, increasing number of studies for almost two decades show that generalist birds act as alternative pollinators in Asia (Roguz et al, 2018). Remarkably, generalist passerines have been demonstrated as the most effective pollinators for winter flowering plants in regions where sunbirds are absent, especially in dry seasons and in the islands (Chen et al, 2019). These include species such as Fritillaria imperialis (Roguz et al, 2021), Firmiana spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zygomorphy has evolved independently in many angiosperm lineages [1]. Within the Lamiales, the flowers of many outcrossing zygomorphic lineages in the Gesneriaceae show diversification in size, shape, and color that are associated with pollination specializations [2][3][4]. Species in the genus Sinningia (subfamily Gesnerioideae, tribe Gesnerieae) are remarkably diverse, with flowers that have features consistent with bee, hummingbird, bat, and moth pollination syndromes [5].…”
Section: Introductionmentioning
confidence: 99%